PENGARUH KEBUTUHAN AIR IRIGASI TERHADAP PENURUNAN MUKA AIR TANAH MENGGUNAKAN MODFLOW-USG DI SRAGEN, JAWA TENGAH - Azizah, Nuraini; Suprapto, Heri (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2022)
One of the determining factors in food security is the availability of agriculture water. Due to decreasing of rainfall and runoff, groundwater is one of the solutions for attaining agriculture's water needs. Groundwater has been depleted in the western region of Sragen Regency. It is necessary to investigate the groundwater level depletion in Sragen Regency so that production can be increased without overexploitation. MODFLOW-USG was used to simulate groundwater conditions mathematically. The model is based on current conditions and projected until 2033, with various scenarios for irrigation necessity which has 1, 0.8 and 0.7 l/s/ha that represented as conventional, System of Rice Intensification (SRI), and Alternate Wetting And Drying (AWD). For current conditions, model results show that groundwater level (GWL) decreased by 7.9 m from 1996 – 2019 without a scenario. Simulations from 2020 to 2033 using conventional water necessity show a decrease in GWL up to 2.585 m, 1.895 m for the SRI method, and 1.788 m for the AWD method. According to this result, the AWD water necessity is the most effective both in reducing groundwater table declining and maintaining plant productivity. However, the decreasing in GWL would occur as long as groundwater withdrawal continued, regardless of the scenario. Therefore, it is proposed to fulfill agricultural land’s water with other water resources such as reservoir or retention basins. Furthermore, there is a need for cropping patterns and scheduling that affect the amount of water demand, so water needs are met and do not over-exploiting the groundwater.Keywords: Groundwater, MODFLOW-USG, conventional, SRI, AWD